Samobójstwo: Śmierć jako przemiana radykalna - Stawiszyński, Tomasz (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
In this article the author tries to examine the idea of suicidal tendencies and their meaning for the soul – in the context of James Hillman’s archetypal psychology. In his groundbreaking book entitled Suicide and the Soul Hillman shows that the medical model – in which suicide is always seen as something pathological – is not suffi cient for understanding this phenomenon. Rather than it being a pathology, says Hillman, suicide is just one of the possibilities that every human can choose from. The most important question is why the psyche would want to enter into the death experience? Hillman says that the suicide impulse is actually a hidden desire for a radical existential, spiritual and psychological change. If one lets this change happen in the process of analysis, i.e. if one lets in theexperience of death without medicalizing and pathologizing it – a literal death of the body is no longer necessary. Death – like the mythological Hades – is always present and that is why the “death experience” is psychologically real, although logically paradoxical.